A bricolage exploration in genkan space: tengu and adjunct TEFL in the Japanese university context. Issue 4 (20th April 2016) - Whitsed, Craig; Wright, Peter
Abstract : This paper reports on research focusing on a group of adjunct teachers of English employed in Japanese universities. Grounded in interpretive epistemology foregrounding constructionist traditions, this research employed bricolage as way of inquiring into, then representing, these teacher's experiences utilising multi-perspectival, multi-theoretical and multi-methodological approaches. Employing elements of Turnerian liminality and blending these with Japanese cultural mythology, this paper explores participants' experience, knowledge and identity. Through interviews and focus groups, participants ( n  = 43) gave voice to their lived world in Japanese universities locating their 'place' as simultaneously inside and outside the boundaries of mainstream Japanese society and universities. As 'liminal personas', participants likened themselves to a 'necessary evil' in the context of internationalising the curriculum. Thus, their condition is understood to be both ambiguous and paradoxical. The Japanese university is likened to genkan (a common architectural feature in Japanese houses resembling an entrance hall or transitional space between inside and outside worlds) space and employing Japanese mythology, it is argued these teachers share features attributed to Tengu ( Tengu are goblin-like monsters in Japanese mythology with long noses and bright red faces who traditionally act in mischievous, disruptive ways).